How Not to Define Poverty: An Anthropological Understanding of Poverty in Yoruba Philosophy - Ademowo, Adeyemi Johnson (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
There is an agreement among scholars that there is no 'one fits all' definition of poverty. Diverse reasons can be adduced for this agreement. This paper seeks to unravel the definition and cultural perception of poverty using the Yorubas of Southwestem Nigeria as a case study. Poverty among the Yorubas is generally perceived as an amalgam of diseases that requires more than money/income, capability development or empowerment, but also spiritual efforts to 'cure'. The essence of this preoccupation is to call the attention of scholars, and public policy experts, to the need to be mindful of local understanding of poverty and consider a holistic analysis of poverty while formulating or reviewing poverty reduction or eradication policies.